1966
DOI: 10.1037/h0023026
|View full text |Cite
|
Sign up to set email alerts
|

Sexual motivation.

Abstract: Imagine that you get such certain awesome experience and knowledge by only reading a book. How can? It seems to be greater when a book can be the best thing to discover. Books now will appear in printed and soft file collection. One of them is this book sexual motivation. It is so usual with the printed books. However, many people sometimes have no space to bring the book for them; this is why they can't read the book wherever they want.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

1974
1974
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 16 publications
1
53
0
4
Order By: Relevance
“…Whalen, 1966;also Bancroft, 1989, who considered sexual arousability, or ''central arousability,'' to be one of the dimensions of sexual appetite).…”
Section: Defining Sexual Desirementioning
confidence: 97%
“…Whalen, 1966;also Bancroft, 1989, who considered sexual arousability, or ''central arousability,'' to be one of the dimensions of sexual appetite).…”
Section: Defining Sexual Desirementioning
confidence: 97%
“…In Study 1, the self-identified asexuals reported engaging in behaviors that they recognized were considered sexual by most people (e.g., genital touching), but that they themselves did not associate with pleasurable sexual arousal. Sexual arousability has been defined as an individual"s characteristic rate of approach to orgasm as a result of sexual stimulation (Whalen, 1966). If asexuals have a higher threshold to experience sexual arousal, their scores on scales assessing sexual arousability and related constructs should be significantly lower than non-asexual individuals.…”
Section: Studymentioning
confidence: 99%
“…In order to have sex, we must first be able to respond to hormonal and neurochemical changes that signal our own sexual desire and arousal and distinguish it from other sympathetic activation, such as anxiety. This ability underlies our moment-to-moment level of sexual arousability (as conceived by Whalen, 1966) and defines a large part of the internal state that is commonly referred to as ''sex drive.'' Second, we must be able to make sense of external cues that signal sexual attraction and receptivity in others (e.g., Salu, 2011).…”
Section: Introductionmentioning
confidence: 99%